Efektivitas Pola Komunikasi Interpersonal Kepala Sekolah dan Guru - Khoirun Nisa Zein Lubis; Garum; Azqiya Aqidatul Izzah (Yayasan Salam Cerdas Al-Fattah, 2025)
This study aims to analyze the interpersonal communication patterns between the principal and teachers at TK IT Insan Robbani Sibuhuan, Padang Lawas Regency. The research problem arises from the finding that two-way communication between the principal and teachers has not been fully optimized, indicated by a lack of openness, delayed feedback, and a low frequency of face-to-face interactions. This study employs a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, and were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings reveal that the principal’s interpersonal communication patterns are implemented through two main forms: verbal and written communication. Supporting factors include a sense of togetherness, teacher loyalty, and adequate communication media, whereas inhibiting factors consist of limited time and differences in teacher workloads. Overall, verbal interpersonal communication is more effective in enhancing teacher motivation, discipline, and performance in the learning process.